Correlation Between MRI Characteristic of Osteosarcoma with 2-Year Survival Outcomes - Mohd Noor Akmal Adam; Emilia Rosniza Mohammed Rusli; Erica Yee Hing; Juliana Fairuz Maktar; Ckhai Loh; Nor Hazla Mohamed Haflah; Faizah Mohd Zaki (Diagnostics)
Background: Magnetic resonance imaging (MRI) plays a crucial role in staging and preoperative evaluation in osteosarcoma patient. Fewer studies have focused on 2-year survival, which reflects tumour aggressiveness and early disease progression. This study examines the association between MRI characteristics and 2-year survival outcomes in osteosarcoma to better understand the imaging characteristic of high-risk patients. Methods: A retrospective case–control study was conducted at a tertiary university hospital. Patients diagnosed with osteosarcoma between 2010 and 2022 were included if they had a pre-treatment MRI and at least 2 years of follow-up. MRI scans were reviewed by two blinded radiologists to assess tumour location, volume, growth pattern, presence of fluid–fluid levels (FFL), pathological fractures, skip metastases, neurovascular bundle involvement, regional lymphadenopathy, and physeal or joint involvement. Statistical analyses, including Fisher’s exact test, Chi-square test, and Mann–Whitney U test, were performed to determine associations between MRI features and survival outcomes. Results: Twenty-eight patients (n = 28) met the inclusion criteria. Larger tumour volume (>300 mls) was significantly associated with poorer 2-year survival (p = 0.008). The presence of skip metastases also correlated with worse outcomes (p = 0.041). While presence of FFL, concentric growth pattern, regional lymphadenopathy, and physeal involvement showed trends toward poorer prognosis, these associations were not statistically significant. Conclusions: MRI characteristics, particularly tumour volume and skip metastases, are significant prognostic indicators of 2-year survival in osteosarcoma. These findings highlight the potential role of MRI in risk stratification and treatment planning, aiding in the identification of high-risk patients that can help with management.